2013
DOI: 10.1016/j.jcf.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of CF lung pathogens: Current status and future potential

Abstract: Molecular diagnostic tests, based on the detection and identification of nucleic acids in human biological samples, are increasingly employed in the diagnosis of infectious diseases and may be of future benefit to CF microbiology services. Our growing understanding of the complex polymicrobial nature of CF airway infection has highlighted current and likely future shortcomings in standard diagnostic practices. Failure to detect fastidious or slow growing microbes and misidentification of newly emerging pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…Due to their known virulence in CF, the major pathogens P. aeruginosa and S. aureus must be treated in priority. However, as described by Aravantagi et al [11], some patients receiving [21]. It should be noticed that even if Beucher et al [7] suggested that the association Nocardia/Pseudomonas seems to be correlated to increased symptoms, in our study, only four sputa contained P. aeruginosa and only two of them were associated with acute exacerbations.…”
Section: Discussionsupporting
confidence: 44%
“…Due to their known virulence in CF, the major pathogens P. aeruginosa and S. aureus must be treated in priority. However, as described by Aravantagi et al [11], some patients receiving [21]. It should be noticed that even if Beucher et al [7] suggested that the association Nocardia/Pseudomonas seems to be correlated to increased symptoms, in our study, only four sputa contained P. aeruginosa and only two of them were associated with acute exacerbations.…”
Section: Discussionsupporting
confidence: 44%
“…2 and Table S1). A probable reason for the higher prevalences is the increased sensitivity inherent in molecular-based approaches when compared to culture-based methods [7]. SIMPER analysis revealed that all recognised pathogen OTUs, with the exception of A. xylosoxidans, contributed substantially to the dissimilarity between lung disease categories ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A relatively small group of bacterial species, all of which can be readily isolated using conventional aerobic culture-based approaches, are associated with chronic lower respiratory infection in CF, including Pseudomonas aeruginosa, Staphylococcus aureus, Burkholderia cepacia complex, Haemophilus influenzae, Stenotrophomonas maltophilia and Achromobacter xylosoxidans [1]. Culture-based approaches have influenced everything from the way infections are treated to informing national CF registries on changing pathogen prevalences with age [6,7]. However, molecular approaches have elucidated a much more complex picture of polymicrobial lower airway infection in this disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no readily available methodology to identify all of these organisms in a way that makes this information valuable for clinical treatment (77). Studies are under way to develop technologies to allow molecular identification without prior culture (78). The choice of antibiotics for pulmonary exacerbations associated with multiple bacteria is an area that has not been extensively studied.…”
Section: Treating Multiple Infectionsmentioning
confidence: 99%